2022
DOI: 10.1016/s2214-109x(21)00506-4
|View full text |Cite|
|
Sign up to set email alerts
|

Alcohol consumption and oesophageal squamous cell cancer risk in east Africa: findings from the large multicentre ESCCAPE case-control study in Kenya, Tanzania, and Malawi

Abstract: Background The contribution of alcohol to the large burden of oesophageal squamous cell carcinoma (ESCC) in east Africa remains uncertain and difficult to assess owing to complex consumption patterns of traditional and commercial drinks. We aimed to assess whether alcohol drinking, overall and at specific intake levels, contributes to ESCC risk in east Africa. MethodsWe did a hospital-based case-control study in Kenya, Tanzania, and Malawi, which included comprehensive assessment of a variety of locally consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…In the ESCCAPE (Esophageal Squamous Cell Carcinoma African Prevention Research) study, a large multicentre case–control study including participants from three Eastern African countries, participants from Tanzania and Kenya, who consumed between 350 and 699 g of ethanol per week, presented an approximately 2- and 3-fold higher risk of ESCC, respectively, than never drinkers; those who consumed at least 700 g of ethanol per week presented 6- and 4-fold higher risk, respectively. No significant differences were observed for ESCC risk, across different levels of ethanol intake, for Malawi participants [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the ESCCAPE (Esophageal Squamous Cell Carcinoma African Prevention Research) study, a large multicentre case–control study including participants from three Eastern African countries, participants from Tanzania and Kenya, who consumed between 350 and 699 g of ethanol per week, presented an approximately 2- and 3-fold higher risk of ESCC, respectively, than never drinkers; those who consumed at least 700 g of ethanol per week presented 6- and 4-fold higher risk, respectively. No significant differences were observed for ESCC risk, across different levels of ethanol intake, for Malawi participants [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The median (percentile 25-percentile 75) number of cigarettes consumed per day was 6 (3-15) among ex-smokers and 5 (3-10) among smokers. The median (percentile 25-percentile 75) years of tobacco consumption was 17(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) among ex-smokers and 31 (25-40) among smokers…”
mentioning
confidence: 99%
“…We welcome the comments by Jin Zhang and colleagues on our study, 1 which reported the strong role of alcohol consumption in oesophageal squamous cell cancer (ESCC) in east Africa. Our findings, which showed that alcohol consumption was a risk factor for ESCC, are consistent with the IARC monographs.…”
mentioning
confidence: 89%
“…In East Africa Middleton, Mmbaga [ 6 ] among males, a substantial part of Oesophageal Squamous Cell Carcinoma would be eliminated by abstention from or minimising alcoholic consumption. Leslie, Ahern [ 7 ] observed in South Africa variables that influence to reduce alcohol-related harms and dependency that offered new opportunities for improving population health.…”
Section: Literature Reviewmentioning
confidence: 99%